PENERAPAN MODEL COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA SMAN 3 BENGKALIS - NURHADI NURHADI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2022)
This research is a classroom action research (PTK) with the application of a jigsaw type cooperative learning model to improve physics learning outcomes. The Jigsaw type cooperative learning model is a cooperative learning model with students learning in small groups consisting of 4-6 people heterogeneously, working together, positively interdependent and responsible for completing the part of learning material that must be learned and delivered to group members. The problem to be solved is the low physics learning outcomes of class XII MIA 2 in Bengkalis Public High School 3 involving 28 students. This study consisted of 2 cycles, in each cycle consisting of four stages, namely Planning, Implementation, Observation and Reflection. In the pre-cycle process, the percentage of student learning completeness is 28.57 %, then after learning the first cycle with the application of the Jigsaw Cooperative Learning Type model there is an increase in the percentage of learning completeness to 64.29 %. And in the second cycle managed to achieve a significant percentage of completeness of 78.57 %. The results showed that there was an increase in student physics learning outcomes as the Jigsaw Cooperative Learning Learning model was implemented. ABSTRAKPenelitian ini merupakan penelitian tindakan kelas (PTK) dengan penerapan model pembelajaran cooperative learning tipe jigsaw untuk meningkatkan hasil belajar fisika. Model pembelajaran cooperative learning tipe Jigsaw merupakan model pembelajaran kooperatif dengan siswa belajar dalam kelompok kecil terdiri dari 4-6 orang secara heterogen, bekerja bersama, saling bergantung positif dan bertanggung jawab atas ketuntasan bagian materi pembelajaran yang harus dipelajari dan disampaikan kepada anggota kelompok. Masalah yang hendak dipecahkan adalah rendahnya hasil belajar fisika kelas XII MIA 2 di SMA Negeri 3 Bengkalis yang melibatkan 28 orang siswa. Penelitian ini terdiri dari 2 siklus, pada setiap siklus terdiri dari empat tahapan, yaitu Perencanaan, Pelaksanaan, Observasi dan Refleksi. Pada proses prasiklus, persentase ketuntasan belajar siswa yaitu sebesar 28,57 %, kemudian setelah dilaksanakan pembelajaran siklus I dengan penerapan model pembelajaran Cooperative Learning Tipe Jigsaw ada peningkatan persentase ketuntasan belajar menjadi 64,29 %. Dan pada siklus II berhasil mencapai persentase ketuntasan yang signifikan sebesar 78,57 %. Hasil penelitian menunjukkan bahwa terjadi peningkatan hasil belajar fisika siswa seiring diterapkannya model pembelajaran Cooperative Learning Tipe Jigsaw.